Enriched enrollment: definition and effects of enrichment and dose in trials of pregabalin and gabapentin in neuropathic pain. A systematic review. - Straube, S; Derry, S; McQuay, H; Moore, R (2008)
AIMS: Enriched enrollment study designs have been suggested to be useful for proof of concept when only a proportion of the diseased population responds to a treatment intervention. We aim to investigate whether this really is the case in trials of pregabalin and gabapentin in neuropathic pain. METHODS: We defined 'complete', 'partial' and 'non-enriched' enrollment, and examined pregabalin and gabapentin trials for the extent of enrichment and for effects of enrichment on efficacy and adverse event outcomes. RESULTS: There were no studies using complete enriched enrollment; seven trials used partial enriched enrollment and 14 non-enriched enrollment. In pregabalin trials the maximum extent of enrichment was estimated at about 12%. Partial enriched enrollment did not change estimates of efficacy or harm. Over 150-600 mg maximum daily dose there was strong dose dependence for pregabalin. CONCLUSIONS: A benefit of partial over non-enriched enrollment could not be demonstrated because the degree of enrichment was rather small, and possibly because enrichment produced little enhancement of treatment effect. Whether a greater degree of enrichment would result in important differences is unknown. Researchers reporting clinical trials with any enrichment must describe both process and extent of enrichment. As things stand, the effects of enriched enrollment remain unknown for neuropathic pain trials.